Un libro di poesia, una struttura vivente (Materiali di Estetica. Terza serie, 2020)
This text is a reflection on poetics, about the making of poetry and its relationship with planning. Latent within the weave of language, in the first long phase of writing texts, the project gradually takes shape when one senses the need for a form to encompass the texts, and to give birth to a book. A living structure, capable of receiving and generating meaning, by enabling a movement, a transformation, to take place between the first and the last page.
Keywords: Circular structure; Project; Blank pages